FDI and Trade Openness in the Tourism Market in Asian Emerging Market Economies (International Journal of Scientific Research and Management (IJSRM), 2022)
FDI and trade openness are considered development tools in all sectors, and the tourism sector is no exception. We examine the impact of inward FDI and trade openness on tourism in selected Asian emerging markets using panel data from the Autoregressive Distributed Lag of the Pooled Mean Group model and examine the direction of the causality of inward foreign direct investment and trade openness on tourism using the Granger causality test for the period 1996-2019. In our research model, we employed the number of tourists’ arrivals as the dependent variable and inward foreign direct investment and trade openness as the main independent variables. The control variables are as follows: GDP growth rate, inflation, mobile telephone subscriptions, and the global financial crisis of 2008. According to the pooled mean group ARDL estimation results, inward FDI, trade openness, GDP growth rate, inflation, and mobile telephone subscription variables had long-run significance in explaining tourism, whereas the global financial crisis dummy variable did not explain tourism arrivals. In the short run, an increase in the GDP growth coefficient attracted more international tourists to Asian EMEs, whereas an increase in inflation reduced tourism arrivals. The study found that there is a unidirectional relationship between FDI inflows and tourism arrivals, with the causality flowing from tourism to FDI. Furthermore, the results of the causality test implied that there were bidirectional connections between tourism and trade openness in Asian emerging markets. The study suggests that emerging economies should also promote short-term policies to increase international tourism by increasing trade openness and foreign direct investment.